Visfatin level in patients with colorectal adenoma - Fazeli, Mohammad Sadegh (Med J Islam Repub Iran, 2016)
Background: Visfatin is an adipocytokine secreted by visceral adipose tissue. It has been shown that adipocytokines may contribute to the induction of carcinogens and progression of tumors. Previously, we found a significant increase in the visfatin serum level in colorectal cancer patients. Herein, we investigated if this cytokine increases in patients with colorectal adenoma as a precursor of colorectal cancer. Methods: In this case-control analytic study, a total of 34 patients diagnosed with colorectal adenoma and 35 disease-free controls were included. Adenomas were also categorized based on their location within the colon. Visfatin serum levels were measured in all cases and controls using enzyme- linked immunosorbent assay kits. In order to compare visfatin levels between groups a twotailed t-test was considered. Pearson correlation was also used to assess the relationship between visfatin levels and other measured variables. Results: Patients included 18 male (53%) and 16 female (47%) with a mean±SD age of 48.3±10.96 years and controls were 18 male (51%) and 17 female (49%) with a mean±SD age of 51.6±12.52 years. There were no significant difference in terms of the visfatin level between the two groups (6.7±3.01 ng/ml for patients and 6.8±2.49 ng/ml for controls, p>0.05). Except for a significant correlation between the BMI and visfatin level (p=0.041), no other correlation was detected. We found no significant difference between the levels of visfatin in each location of adenoma comparing the healthy controls (p>0.05 in all comparisons). There was no statistical difference between the locations groups in terms of visfatin level as well (p>0.05). Conclusion: Visfatin serum level does not significantly increase in patients with colorectal adenoma. Site of adenoma within the colon or rectum does not seem to play an important role in this regard as well.